Whole corn rations for finishing heifers: A comparison of self-fed and mixed supplement, with and without salt - L.H. Harbers; K.F. Harrison; D. Richardson; E.F. Smith (Kansas Agricultural Experiment Station Research Reports, 1972)
Twenty-four Hereford x Angus heifers averaging 714 lbs. were allotted by weight to four groups of six animals each to study effects on gain, feed intake, and feed efficiency of: 1. Free-choice whole corn without roughage. 2. Protein supplement either mixed with whole corn or supplied seperately (free-choice). 3. Omitting salt
Keywords: Cattlemen' s Day; 1972; Report of progress (Kansas State University. Agricultural Experiment Station); 557; Beef; Corn; Finishing heifers; Salt